2019
DOI: 10.1530/eje-19-0383
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, body composition and metabolic profiles in adult women with complete androgen insensitivity syndrome and removed gonads using oral or transdermal estrogens

Abstract: Objectives To assess bone health in adult women with complete androgen insensitivity syndrome (CAIS) and removed gonads compared with age-matched healthy controls. To evaluate the effects of transdermal oestradiol 2 mg or oral estradiol valerate 2 mg on bone, biochemical and clinical characteristics. Design Cohort study. Methods Bone, body composition and anthropometric parameters were assessed in 32 adult CAIS and 32 healthy controls. In 28 cases, CAIS evaluations of metabolic, bone and body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[11][12][13]. However, the research conclusions regarding the contribution to the adequate maintenance of BMD cannot reach a consensus [14][15][16][17][18][19][20][21][22][23]. Reid et al took the lead in demonstrated that fat mass (FM), one main component of the body weight, is closely related to fat mass in premenopausal women [19].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]. However, the research conclusions regarding the contribution to the adequate maintenance of BMD cannot reach a consensus [14][15][16][17][18][19][20][21][22][23]. Reid et al took the lead in demonstrated that fat mass (FM), one main component of the body weight, is closely related to fat mass in premenopausal women [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite hormone replacement therapy for a mean of 17.4 years, reduced spinal, femoral neck, and total body BMD is noted in women with CAIS who have undergone gonadectomy during their early adolescence. ( 53 ) Oral and transdermal estrogen replacement therapy (2 mg transdermal estradiol or 2 mg oral estradiol valerate) was associated with a small but significant (4.2%) improvement in spinal aBMD over 6 years, in a small subgroup of women in this cohort. Femoral neck and total body BMD were unaffected.…”
Section: Methodsmentioning
confidence: 75%
“…As we have shown before that testosterone might have beneficial effects in terms of sexual desire [5] in comparison to estradiol treatment in women with CAIS, its use may have additional value without any trade-off in terms of safety. There is evidence that women with CAIS have lower bone mineral density [10,40] and this may be due to a combination of insufficient estradiol replacement as well as independent effects of androgen resistance, as androgens are know to have positive effects on bone [42]. However, it is unclear if any potential direct effect of testosterone on bone that is not mediated via aromatization to estradiol is of clinical relevance when adequate estradiol levels are achieved [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although the corresponding dosage was selected on the basis of providing target concentrations according to the manufacturer’s average serum levels within the reference range of men and women from the general population, there is a high inter-individual variance due to differences in transdermal absorption. A dose titration scheme-based protocol might therefore have helped to average out these differences and higher estradiol levels than those achieved on average in our study population, may have further beneficial effects on bone structure [ 39 , 40 ] and metabolic health surrogates [ 41 ]. In addition, anthropometric measures such as body composition and waist/hip circumference were not recorded, therefore we cannot determine if the observed changes in BMI were due to an increase in fat or lean mass or simple water retention.…”
Section: Discussionmentioning
confidence: 99%